(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Fusarium oxysporum f. sp. vasinfestum W.S. Snyder & H.N. Hans isolated from soil during research. Studied the activity of the pathogens and the growth of fungi in a nutrient medium. Isolation of pure cultures of the studied fungus and selection of the selected compounds in various nutrient media Fusarium oxysporum f. sp. vasinfestum W.S. Snyder & H.N. Hans. Studied the growth and development of fungi, the formation of micromacroconidia and the synthesis of metabolites.